158k views
4 votes
Find the inverse of this equationf(n) = (n-3)/ 2

1 Answer

1 vote

Answer:
f^(-1)(n)=2n+3

Explanation:

To find the inverse, first we will set the equation equal to y.

f(n) = (n - 3)/2

y = (n - 3)/2

Next, we will switch the n and y values.

n = (y - 3)/2

Now, we will solve for y.

First, multiply both sides of the equation by 2.

2n = y - 3

Next, add 3 to both sides of the equation.

y = 2n + 3

Lastly, write it with inverse notation.


f^(-1)(n)=2n+3

User Andre Yonadam
by
5.8k points